Practices of teachers from preschools espousing progressive educational philosophy - Vidal, Vijaya Torres; Hizon, Evalyn G. (2008)
As there are different ideologies, there are also different educational ideologies, there are also different philosophies that teachers adhere which serve as their guiding principle in their actual classroom practices. The progressive educational stream was chosen by the researcher with the objective to explore on teachers' views and beliefs about a teacher, a child, a school, education and progressive educational philosophy. Furthermore, the study attempted to investigate how teachers actualize the basic tenets of progressive stream in terms of curriculum, physical environment, daily time schedule and assessment of children. The respondents of this study were 10 female preschool teachers who has more than three years teaching experience in preschools that have existed for more than four years in Metro Manila and Binan, Laguna. These schools are managed and owned by administrators who are graduates and students of Master of Family Life and Child Development in the University of the Philippines, Diliman. Data were gathered through interviews and classroom observation employing an interview schedule and a checklist. Photography and video recordings of the actual class session, as well as collected documentary evidence were used to further support the gathered data. The researcher used a qualitative research design in analyzing the data from individual respondents which were presented in the form of individual case studies. Findings of the study revealed that there were differences between the teachers' beliefs in claiming a "child-centered" approach and the teachers' actual practices. Some of the factors that affect teaching practices are the following: limited space of the school, school budget, the growing concern of parents in preparing children for big schools, the parents' demands on children's academic tasks and the bulk of responsibilities of the teacher. The findings of this study have great implication to progressive teachers and practitioners to be grounded in their philosophy as they teach young children.
Thesis (M. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Women Preschool teachers; Progressive education